2014
DOI: 10.1037/a0035261
|View full text |Cite
|
Sign up to set email alerts
|

Variations in cognitive maps: Understanding individual differences in navigation.

Abstract: There are marked individual differences in the formation of cognitive maps both in the real world and in virtual environments (VE; e.g., Blajenkova, Motes, & Kozhevnikov, 2005; Chai & Jacobs, 2010; Ishikawa & Montello, 2006; Wen, Ishikawa, & Sato, 2011). These differences, however, are poorly understood and can be difficult to assess except by self-report methods. VEs offer an opportunity to collect objective data in environments that can be controlled and standardized. In this study, we designed a VE consisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

33
288
2
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(325 citation statements)
references
References 53 publications
33
288
2
2
Order By: Relevance
“…Complementing these findings, we found that posterior PHC activity was associated with performance on a path integration task, that anterior PHC activity was associated with performance on a Cognitive Map formation task, and that both regions were associated with everyday spatial ability. These observations are consistent with previous reports that individual differences in spatial ability reflect natural variability in PHC function23262728, and support and extend our previous finding that participants who successfully recalled the layout of a complex virtual maze from memory produced an enhanced theta effect (Experiment 3 in Ref. 7).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Complementing these findings, we found that posterior PHC activity was associated with performance on a path integration task, that anterior PHC activity was associated with performance on a Cognitive Map formation task, and that both regions were associated with everyday spatial ability. These observations are consistent with previous reports that individual differences in spatial ability reflect natural variability in PHC function23262728, and support and extend our previous finding that participants who successfully recalled the layout of a complex virtual maze from memory produced an enhanced theta effect (Experiment 3 in Ref. 7).…”
Section: Discussionsupporting
confidence: 92%
“…In another noteworthy study that used a virtual environment modeled after a rat foraging task, Doeller et al (2010) observed that the fMRI BOLD response in human right PHC exhibited a speed-modulated six-fold rotational symmetry in running direction as predicted by theoretical models of theta phase coding. Variations in the structure and function of PHC and surrounding structures have also been observed to contribute to individual differences in human spatial navigation23.…”
Section: Discussionmentioning
confidence: 99%
“…Large-scale spatial ability also describes that ability to learn and navigate environmental information and routes. However, while a perspective-taking ability can be identified as a unique factor, the construct of large-scale spatial ability is more difficult to describe in this way as there is a significant body of evidence illustrating its association with perspective taking, memory and spatial skills such as spatial relations and visualisation (Allen et al 1996;Fields and Shelton 2006;Hegarty et al 2006;Ishikawa and Montello 2006;Kozhevnikov et al 2006;Weisberg et al 2014). Therefore, while the construct of large-scale spatial ability is of significant importance, it is perhaps better thought of as an amalgam of first-order factors when considered through the lens of environmental learning.…”
Section: Evidence Dissociating Mental Perspective Taking and Mental Rmentioning
confidence: 99%
“…Hegarty et al , 2006;Ishikawa, & Montello, 2014;Weisberg, Schinazi, Newcombe, Shipley, & Epstein, 2014;Weisberg & Newcombe, 2016).…”
Section: Discussionunclassified